2019
DOI: 10.1016/j.ebiom.2019.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol-induced degradation of FANCD2 sensitizes pediatric high-grade gliomas to the DNA-crosslinking agent carboplatin

Abstract: BackgroundPediatric high-grade gliomas (pHGG) are the leading cause of cancer-related death during childhood. Due to their diffuse growth characteristics, chemoresistance and location behind the blood-brain barrier (BBB), the prognosis of pHGG has barely improved in the past decades. As such, there is a dire need for new therapies that circumvent those difficulties. Since aberrant expression of DNA damage-response associated Fanconi anemia proteins play a central role in the onset and therapy resistance of man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…At these doses, though effective, systemic toxicities including cardiotoxicity (Liu et al, 2019), hepatotoxicity (Jin et al, 2019), and nephrotoxicity (Wu et al, 2018) have been reported, whereas lower doses, though safe, show limited efficacy. To overcome the toxicity issues while achieving the desired therapeutic efficacy, various drug delivery approaches have been investigated that include combination with other chemotherapeutic agents such as afatinib, axitinib, and gefitinib (Zhang et al, 2014;Choi et al, 2016;Gao et al, 2019;Zhao et al, 2019;Dai et al, 2020), combination with traditional Chinese medicines such as betulinic and ellagic acids (An et al, 2015;Duan et al, 2019), overcoming multidrug resistance (Metselaar et al, 2019), nanoparticulate drug delivery systems (Qi et al, 2014;Hakala et al, 2020;, and combination with nucleic acid (Huang et al, 2017). Among these, nanoparticulate drug delivery systems/ nanoformulations of celastrol have been widely reported as a promising strategy to effectively deliver drug at the target site rendering enhanced efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…At these doses, though effective, systemic toxicities including cardiotoxicity (Liu et al, 2019), hepatotoxicity (Jin et al, 2019), and nephrotoxicity (Wu et al, 2018) have been reported, whereas lower doses, though safe, show limited efficacy. To overcome the toxicity issues while achieving the desired therapeutic efficacy, various drug delivery approaches have been investigated that include combination with other chemotherapeutic agents such as afatinib, axitinib, and gefitinib (Zhang et al, 2014;Choi et al, 2016;Gao et al, 2019;Zhao et al, 2019;Dai et al, 2020), combination with traditional Chinese medicines such as betulinic and ellagic acids (An et al, 2015;Duan et al, 2019), overcoming multidrug resistance (Metselaar et al, 2019), nanoparticulate drug delivery systems (Qi et al, 2014;Hakala et al, 2020;, and combination with nucleic acid (Huang et al, 2017). Among these, nanoparticulate drug delivery systems/ nanoformulations of celastrol have been widely reported as a promising strategy to effectively deliver drug at the target site rendering enhanced efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…The findings not only open new opportunities for the clinical development of SAHA but should also motivate the clinical investigation of celastrol, which has been hampered by its toxicity. On the other hand, celastrol, as a blood-brain barrierpenetrable compound, could degrade FANCD2, to sensitize glioma cells to the archetypical DNA-crosslinking agent carboplatin in vitro in seven patient-derived pediatric highgrade gliomas (pHGG) models (Metselaar et al, 2019). Therefore, combination therapy using celastrol and carboplatin might serve as a clinically relevant strategy for the treatment of pHGG.…”
Section: Overcoming Multidrug Resistancementioning
confidence: 99%
“…Thus, the molecular mechanism of carboplatin resistance occurs through the regulation of Mcl-1 and c-FLIP by the elevation of Nrf2-dependent PSMA5 expression in glioma cells. Recently, there has been a study related to Fanconi anemia group D2 protein (FANCD2) as a modulating factor of carboplatin sensitivity in pediatric high-grade glioma (pHGG) [ 148 ]. pHGG is characterized by epigenetic alterations and defects in DNA damage repair genes and causes the occurrence of malignant brain tumors due to a syndrome called Fanconi anemia, a genetic disorder that results from disruption of the Fanconi DNA repair mechanism [ 149 , 150 ].…”
Section: Resistance Mechanism Of Platinum-based Anticancer Drugs In Brain Tumorsmentioning
confidence: 99%
“…In addition, carboplatin induced sensitivity to FANCD2-dependent DNA crosslinking in glioma cells. Thus, these findings show that FANCD2 regulation acts as a strategy to overcome chemical resistance in pHGG [ 148 , 153 ].…”
Section: Resistance Mechanism Of Platinum-based Anticancer Drugs In Brain Tumorsmentioning
confidence: 99%